2021
DOI: 10.1108/bfj-07-2020-0637
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic content, antioxidant, anti-inflammatory and anti-microbial potentials of Bambara groundnut (Vigna subterranea L.) seed extract

Abstract: PurposeBambara groundnut is a hard-to-cook grain and this has limited its utilisation to some extent. However, the grain is a good source of phytochemicals with antioxidant properties. This study investigated the total phenol content, antioxidant, anti-inflammatory and anti-microbial potentials of hot-water extract of four Bambara groundnuts differentiated by their seed coats (cream, black, maroon and brown).Design/methodology/approachBambara grains were heated in water at a ratio 1:20 (w/v) and the grains bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Similarly, Oyeyinka et al. ( 2021 ) found higher moisture in cream BGN flour than in red and brown BGN flours. The ash content of all BGN flours was not significantly ( p < .05) different from each other, with values varying from 2.89% to 3.39%.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Oyeyinka et al. ( 2021 ) found higher moisture in cream BGN flour than in red and brown BGN flours. The ash content of all BGN flours was not significantly ( p < .05) different from each other, with values varying from 2.89% to 3.39%.…”
Section: Resultsmentioning
confidence: 82%
“…disparity in TPC(Oyeyinka et al, 2021). Therefore, BGN grains that are darker in coat colors possess higher TPC than those with lighter coat colors(Adedayo et al, 2021;Parikh & Patel, 2018) Oyeyinka et al (2017).…”
mentioning
confidence: 98%
“…The black whole seed had the highest (p < 0.05) antioxidant activity (84.4 μmol AAE/g) followed by red (64.9 μmol AAE/g), mixture (52.4 μmol AAE/g), brown (50.5 μmol AAE/g), brown-eye (37.9 μmol AAE/g) and black-eye whole seed (34.5 μmol AAE/g). Oyeyinka et al 37 reported black and maroon BGN seed hot-water extracts showing the highest FRAP values when compared to brown and cream BGN seed hot-water extracts. Oyeyinka et al 37 further noted that high antioxidant activities in black and brown BGN seed extracts when compared to other seeds, could be as a result of increased concentration of protic flavonoids in the BGN seed coats.…”
Section: Resultsmentioning
confidence: 99%
“…Oyeyinka et al 37 reported black and maroon BGN seed hot-water extracts showing the highest FRAP values when compared to brown and cream BGN seed hot-water extracts. Oyeyinka et al 37 further noted that high antioxidant activities in black and brown BGN seed extracts when compared to other seeds, could be as a result of increased concentration of protic flavonoids in the BGN seed coats. A significant difference (p < 0.05) in FRAP existed between black and red whole seed, red, mixture and brown as well as brown-eye and black-eye seed extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation